Cystophora Nilsson 1820 ... - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Cystophora Nilsson 1820 Cystophora Nilsson 1820, Skand. Faun. Dagg. Djur., Vol. 1: 382. Type Species: Cystophora borealis Nilsson 1820 Synonyms: Semmatopis Gloger 1841; Stemmatops Van der Hoeven 1855; Stemmatopus F. G. Cuvier 1826. Species and subspecies: 1 species: Species Cystophora cristata (Erxleben 1777) Discussion: Revised by King (1966). ... : Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Carnivora, pp. 532-628 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 595, DOI: 10.5281/zenodo.7316519 ...